2020
DOI: 10.1038/s41598-020-77737-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging with a megapixel SPAD camera and neural network lifetime estimation

Abstract: Fluorescence lifetime imaging microscopy (FLIM) is a key technology that provides direct insight into cell metabolism, cell dynamics and protein activity. However, determining the lifetimes of different fluorescent proteins requires the detection of a relatively large number of photons, hence slowing down total acquisition times. Moreover, there are many cases, for example in studies of cell collectives, where wide-field imaging is desired. We report scan-less wide-field FLIM based on a 0.5 MP resolution, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 67 publications
(76 reference statements)
1
45
0
Order By: Relevance
“…com/inatamara/NyxSense) and could be used by the community to test, further improve, or simply use the methodology we proposed. Spectrally resolved FLIM is readily available commercially, and several bespoke implementations aimed to make available cost-effective and user-friendly solutions have been also published (e.g., [6,42,43,51,56,58,61,63,76], promising increased availability of such sophisticated assays in the near future. We showed that the combination of spectrally resolved time phasors (sTP → ) with the spectral phasors (SP or TSP) permitted efficient demixing of three FRET pairs, presenting a low level of direct acceptor excitation using only six control signatures.…”
Section: Discussionmentioning
confidence: 99%
“…com/inatamara/NyxSense) and could be used by the community to test, further improve, or simply use the methodology we proposed. Spectrally resolved FLIM is readily available commercially, and several bespoke implementations aimed to make available cost-effective and user-friendly solutions have been also published (e.g., [6,42,43,51,56,58,61,63,76], promising increased availability of such sophisticated assays in the near future. We showed that the combination of spectrally resolved time phasors (sTP → ) with the spectral phasors (SP or TSP) permitted efficient demixing of three FRET pairs, presenting a low level of direct acceptor excitation using only six control signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Following on this work, Zickus et al. 96 used an MLP trained with simulated data [ Figs. 3(a) and 3(b) ], in combination with image stitching, to retrieve a 3.6-megapixel ( ) wide field FLIM image reconstruction using a time-resolved single-photon avalanche diode (SPAD) array.…”
Section: Deep Learning For Macroscopic Fluorescence Lifetime Imagingmentioning
confidence: 99%
“…Additionally, multispectral FLIM was implemented by Ghezzi et al 9 using an 18 × 1 linear SPAD array. Moreover, Zickus et al 10 aimed for real-time FLIM using a time-gated SPAD array capable of achieving widefield FLIM of 500 × 1024 pixels with lifetime estimation performed by a custom artificial neural network (ANN) that was trained on simulated lifetime decay curves. Given the advantages of the SPAD array (Table 1), this technology is likely to increase in popularity for FLIM.…”
Section: Wide-field Flimmentioning
confidence: 99%